Partnership Strategy for Phase II (2017-2022): CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) - CGIAR Research Program on Climate Change, Agriculture and Food Security (2016)
The CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) works with a wide range of institutions in research, government, civil society and the private sector, to find realistic strategies to deal with climate change as it affects and is affected by agriculture and food security. The program includes 41 strategic partners and over 700 partners worldwide.